An experimental investigation on thermal stratification characteristics with PCMs in solar water tank. (1st January 2019) - Huang, Huajie; Wang, Zilong; Zhang, Hua; Dou, Binlin; Huang, Xiuhui; Liang, Hao; Goula, Maria A.
Highlights: Effect of the positions of the PCMs on thermal stratification at various flow rates was analysed. Higher flow rate resulted in an earlier inflection point time. Lower position of the PCMs resulted in better thermal stratification in the water tank. Fill efficiency was used as a measurement index to assess the performance of the thermal storage tank. Abstract: Thermal storage technology with phase-change materials (PCMs) is an important approach for improving solar energy utilisation efficiency. In this study, for analysing the stratification of a thermal tank with PCMs at an initial water temperature of 353.15 K and inlet water temperature of 278.15 K, a thermal storage tank containing sodium acetate trihydrate with a phase change temperature of 325.15 K and super-cooling temperature below 278.15 K was developed. This study thoroughly investigated the effect of the positions of the PCMs on thermal stratification characteristics at various flow rates (0.06, 0.18, 0.3, 0.42, and 0.54 m 3 /h) and with increasing dimensionless time. This study further examined the fill efficiency, which was compared with the exergy efficiency, MIX number, and Richardson number to characterise the stratification of the thermal tank. The experimental results demonstrated that when the temperature of the water storage tank increased from 278.15 K to 353.15 K, the energies of the water tank and PCM tank were 18.81 and 19.34 MJ, respectively. At the same inlet flow rate, increasing the PCMs close to the inlet resulted in improved thermal stratification of the tank. With high flow rates, the cold–hot water mixing intensified and the thermocline thickness in the tank increased, thereby weakening the thermal stratification. Moreover, as the water-release process progressed, the cold–hot water mixing in the water tank tended to be stable, thereby forming a stable thermocline. The thermal stratification of the ordinary tank was superior to that of the PCM tank. However, as the PCMs were located at the bottom of the water tank, the thermal stratification was optimal when the inlet flow rate was higher than 0.42 m 3 /h.